1999
DOI: 10.1128/jb.181.20.6361-6370.1999
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phase-Dependent Variation in Protein Composition of the Escherichia coli Nucleoid

Abstract: The genome DNA of Escherichia coli is associated with about 10 DNA-binding structural proteins, altogether forming the nucleoid. The nucleoid proteins play some functional roles, besides their structural roles, in the global regulation of such essential DNA functions as replication, recombination, and transcription. Using a quantitative Western blot method, we have performed for the first time a systematic determination of the intracellular concentrations of 12 species of the nucleoid protein in E. coli W3110,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
243
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 803 publications
(253 citation statements)
references
References 66 publications
7
243
0
3
Order By: Relevance
“…Combined with our data, this fact suggests that the activity of VjbR is dependent on IHF which is a bending factor acting on the virB promoter topology to allow transcription to proceed. The timing of expression of virB in late exponential phase could then be related to the increasing expression of IHF‐encoding genes preparing the starvation response of the cells in stationary phase as described in other bacteria (Ali Azam et al ., 1999). This hypothesis is coherent with the observation that in minimal medium virB is expressed in early exponential phase (Boschiroli et al ., 2002; Sieira et al ., 2004) and that the alarmone of the stringent response ppGpp, known to control the expression and the activity of IHF (Aviv et al ., 1994), is crucial for virB expression (M. Dozot and S. Köhler, pers.…”
Section: Discussionmentioning
confidence: 88%
“…Combined with our data, this fact suggests that the activity of VjbR is dependent on IHF which is a bending factor acting on the virB promoter topology to allow transcription to proceed. The timing of expression of virB in late exponential phase could then be related to the increasing expression of IHF‐encoding genes preparing the starvation response of the cells in stationary phase as described in other bacteria (Ali Azam et al ., 1999). This hypothesis is coherent with the observation that in minimal medium virB is expressed in early exponential phase (Boschiroli et al ., 2002; Sieira et al ., 2004) and that the alarmone of the stringent response ppGpp, known to control the expression and the activity of IHF (Aviv et al ., 1994), is crucial for virB expression (M. Dozot and S. Köhler, pers.…”
Section: Discussionmentioning
confidence: 88%
“…To differentiate these two possibilities, we tracked the diffusion of a chromosomal DNA segment labeled with six tetO operator sites ( tetO 6 ) tightly bound by TetR-mCherry fusion protein molecules under the same cell growth and imaging conditions as HUα-PAmCherry (Figure S6A). Note that compared to other fluorescent repressor-operator systems (FROS) using tandem arrays of hundreds of DNA binding sites 37 , the small footprint of the tetO 6 site (∼200 bp) enabled us to pinpoint the position of the labeled chromosomal DNA with high accuracy and negligible perturbations 38 . We observed that TetR-PAmCherry formed distinct fluorescent spots in cells (Figure S6A), consistent with its specific DNA binding property.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli HU has two subunits of ∼9 kDa each, α and β, which form either HUα 2 homodimers or HUαβ heterodimers depending on the growth phase (HUβ 2 homodimers were negligible under log-phase growth) 7 . Monomers of HU are not detectable 6, 7 . HU was originally proposed to be the bacterial equivalent to eukaryotic histones due to its small size, lack of sequence specificity, and its in vitro ability to generate condensed plasmid DNA 8 and to induce negative supercoils in relaxed plasmid DNA in the presence of topoisomerase I 9 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Adaptive molecular strategies ensure the ability of microorganisms to survive in environments significantly different from those, optimal for their growth, and have been the subject of active research over the past years [2][3][4][5][6][7][8]. Such adaptive strategy often launch the increasing synthesis (up to 150-200 thousand copies) of a ferritin-like protein Dps (DNA-binding protein of starved cells) [9][10][11][12]. Dps carries on a regulatory and protective role within Escherichia Coli (E. coli) cells [13].…”
Section: Introductionmentioning
confidence: 99%